Boosting the Activity and Stability with Dual‐Metal‐N Couplings for Li–O2 Battery. Issue 3 (9th July 2021) - Wu, Shan; Wu, Di; Zhang, Dawei; Liu, Wenhong; Luo, Hao; He, Jianbo; Yang, Qingchun; Li, Zhiwei; Liu, Ruiping
Abstract : Electrocatalysts with high efficiency are crucial for improving the storage capacity and electrochemical stability of lithium–oxygen batteries (LOBs). In this work, through a facile hydrothermal method, cobalt–nitrogen‐doped carbon nanocubes (Co–N/C), the calcination products of zeolitic imidazolate framework (ZIF–67) are encapsulated by ultrathin C–MoS2 nanosheets to obtain Co–N/C@C–MoS2 composites which are used as host materials for the oxygen cathode. The synergistic effect between Co–N x active sites and Mo–N coupling centers effectively promotes the formation and decomposition of Li2 O2 during repeated discharge and charge process. The mesoporous C–MoS2 nanosheets with delicately designed morphology facilitate charge transfer and account for improved reaction kinetics and more importantly, suppressed side reactions between the carbon materials and the electrolyte. The oxygen cathode with the Co–N/C@C–MoS2 host shows a high initial discharge specific capacity of 21 197 mA h g −1 and a long operation life of 332 cycles. Theoretical calculation provides in‐depth explanation for the reaction mechanism and offers insights for the rational design of electrocatalysts for LOBs. Abstract : Through a facile hydrothermal method, cobalt–nitrogen‐doped carbon nanocubes (Co–N/C) are encapsulated by C–MoS2 nanosheets to obtain Co–N/C@C–MoS2 composites which are integrated into the cathode of rechargeable non‐aqueous LOBs. The excellent electrochemical performance can be attributed to the Co–N/Mo–N coupling centers and the protection of MoS2 nanosheets.